Pengaruh Mutasi terhadap Produktivitas dengan Kepuasan Kerja Pegawai sebagai Variabel Intervening: (Studi Kasus pada PT. Pegadaian Syariah Area Pamekasan) - Dian Aditya Kusuma; Wasis Budiarto; C. Sri Hartati (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Dian Aditya Kusuma, 2025. The Influence of Mutations on Productivity with Employee Job Satisfaction as an Intervening Variable (Case Study at PT. Islamic Pawnshop Pamekasan Area). Graduate Program, University Wijaya Putra Surabaya. This explanatory study adopts a quantitative approach, with a sample of 84 participants. The analysis was conducted using Smart PLS (Partial Least Squares). The study aimed to achieve the following objectives: 1) To test and analyze the direct influence of mutations on employee job satisfaction at the Pamekasan Area Islamic Pawnshop Office; 2) To test and analyze the direct influence of mutations on productivity at the Pamekasan Area Islamic Pawnshop Office; 3) To test and analyze the direct influence of job satisfaction on employee productivity at the Pamekasan Area Islamic Pawnshop Office; 4) To test and analyze the indirect influence of mutations on employee productivity through job satisfaction at the Pamekasan Area Islamic Pawnshop Office. The findings of the study indicated that: 1) Mutations have a significant and direct influence on job satisfaction; 2) Mutations have a significant and direct influence on productivity; 3) Job satisfaction has a significant and direct influence on productivity; 4) Mutations have a significant indirect influence on productivity, mediated by job satisfaction. These findings underscore the importance of mutations as a key factor in improving employee productivity, both directly and through its impact on job satisfaction. The results provide valuable insights for improving human resource management practices at PT. Islamic Pawnshop in the Pamekasan Area.